Bridging the gap: Using 3D printed polycaprolactone implants to reconstruct circumferential tracheal defects in rabbits. (24th December 2019) - Chan, David S.; Gabra, Nathalie; Baig, Ayesha; Manoukian, John J.; Daniel, Sam J.
Abstract : Objective: 1) To assess the feasibility of reconstructing 2‐cm‐long circumferential tracheal defects with a 3D printed polycaprolactone (PCL) implant in rabbits. 2) To evaluate endoscopic, histologic, and functional characteristics of a PCL tracheal implant over time. Methods: Ten New Zealand rabbits were included in this study. A 2‐cm‐long 3D printed PCL tracheal implant was created. All rabbits underwent surgical excision of a 2‐cm‐long cm segment of cervical trachea, which was reconstructed with the implant. Rabbits were sacrificed at the following time points: 0, 4, 5, 6, and 7 weeks postoperatively. At these time points, a rigid bronchoscopy was performed, and blinded evaluators calculated the percentage of airway stenosis. The tracheas were then harvested and prepared for histologic analysis. Results: All rabbits survived to their date of sacrifice except for one. Rabbits were euthanized between 0 to 54 days postoperatively with a median of 30 days. All rabbits developed significant granulation tissue with an average percentage stenosis of 92.3% ± 6.1%. On histology, granulation was present with extensive neovascularization and mixed inflammatory cells. There was re‐epithelialization present on the luminal surface of the PCL implant near the anastomoses but absent at the center of the implant. Conclusion: This study demonstrates that our 2‐cm‐long 3D printed PCL tracheal implant can be used to reconstruct a tracheal defect of equivalent size in a New Zealand rabbit model in the short term. However, significant granulation tissue formation limits long‐term survival. Further research is warranted to limit the granulation tissue overgrowth. Level of Evidence: NA Laryngoscope, 2019